EXPERIENCE OF INCLUSIVE EDUCATION IMPLEMENTATION IN EUROPEAN COUNTRIES - Iryna RUDNYTSKA-YURIICHUK; Tetiana KOLTUNOVYCH (Association of Social and Educational Innovation, 2024)
Education has always been a special function of the society and the state, aimed at the formation and development of socially significant qualities of each person as a society member and a citizen of the country. The society's consciousness formation is influenced through education, and the processes of conscious self-development of citizens are regulated. As a social and cultural phenomenon, education is the humanity attribute, its integral supporter in the progressive movement of evolutionary development. The European system of general secondary education with its variety of types and diversity of educational institutions, in particular those that take care of the education of children with special needs, is a key element of the modern European model of the social system, which is attractive to countries with a post-totalitarian regime (including Ukraine) in view of the tasks, goals and prospects of solving urgent problems of a social and pedagogical nature. Starting from the '70s there were changes in the system of special education in advanced European countries, and as a result, integrated and inclusive education of children with developmental disabilities was defined as the main form of their education. The article identifies the conceptual and terminological field of inclusive education; the trends and problems of the inclusive education formation in some European countries are highlighted, in particular, it is about the state policy of supporting inclusive education in Italy, Belgium, Austria, the Netherlands and Sweden.